Use of cffDNA to avoid administration of anti‐D to pregnant women when the fetus is RhD‐negative: implementation in the NHS. (21st August 2014) - Soothill, PW; Finning, K; Latham, T; Wreford‐Bush, T; Ford, J; Daniels, G
<x xml:space="preserve">Abstract</x> Objective To determine whether a policy of offering cffDNA testing to all RhD‐negative women at about 16 weeks' gestation to avoid anti‐D administration when the fetus is RhD‐negative could be implemented successfully in the NHS without additional funding. Design Prospectively planned observational service implementation pilot and notes audit. Setting Three maternity services in the South West of England. Population All RhD‐negative women in a 6‐month period. Methods Prospective, intervention, cross‐sectional observational study, using pre‐intervention data as controls. Main outcome measures Proportion of suitable women who offered and accepted the test. Accuracy of the cffDNA result as assessed by cord blood group result. Fall in anti‐D doses administered. Results 529 samples were received; three were unsuitable. The results were reported as RhD‐positive (n = 278), RhD‐negative (n = 185) or inconclusive, treat as positive (n = 63). Cord blood results were available in 502 (95%) and the only incorrect result was one case of a false positive (cffDNA reported as positive, cord blood negative – and so given anti‐D unnecessarily). The notes audit showed that women who declined this service were correctly managed and that anti‐D was not given when the fetus was predicted to be RhD‐negative. The total use of anti‐D doses fell by about 29% which equated to about 35% of RhD‐negative women not receiving anti‐D in their pregnancy unnecessarily. Conclusions We recommend this service is extended to all UK NHS services.